Synonymous codon usage bias dependent on local nucleotide context in the class deinococci - Cutler R.W. (2014)
To study the evolution of mutation biased synonymous codon usage, we examined nucleotide co-occurrence patterns in the Deinococcus radiodurans, D. geothermalis, and Thermus thermophilus genomes for nucleotide replacement dependent on the surrounding nucleotide context. Nucleotides on the third codon site were found to be strongly correlated with nucleotide sites at most six nucleotides away in all three species, where abundance patterns were dependent on whether two nucleotides share the same purine(R)/pyrimidine(Y) status. In the class Deinococci adjacent third site nucleotides were strongly correlated, where NNR-NNR and NNY-NNY codon pairs were overabundant while NNR-NNY and NNY-NNR codon pairs were underabundant. By far the largest deviations in all three species occur for NN(YR)-(YR)NN codon pairs. In the Thermus species, the NNY-YNN and NNR-RNN codon pairs were overabundant versus the underabundant NNY-RNN and NNR-YNN codon pairs, whereas in the Deinococcus species the opposite over-/underabundance relationship held for adjacent (GC) bases. We also observed a weaker overabundance of NNR-NRN and NNY-NYN codon pairs versus the underabundant NNR-NYN and NNY-NRN codon pairs. The perfect purine/pyrimidine symmetry of each of these cases, plus the lack of significant deviations for nucleotide pairs on other length scales up to 20 codons apart demonstrates that a pervasive pattern of nucleotide replacement dependent on local nucleotide context, and not codon bias, has occurred in these species. This nucleotide replacement has led to modified synonymous codon usage within the class Deinococci that affects which codons are positioned at particular codon sites dependent on the local nucleotide context. © 2008 Springer Science+Business Media, LLC.